Activation of inwardly rectifying Kir2.x potassium channels by β3-adrenoceptors is mediated via different signaling pathways with a predominant role of PKC for Kir2.1 and of PKA for Kir2.2 - Scherer, Daniel; Seyler, Claudia; Kulzer, Martin; Günth-Merker, Myriam Catherine; Scholz, Eberhard P.; Kathöfer, Sven; Thomas, Dierk; Maurer, Martin H.; Kreuzer, Jörg; Bauer, Alexander; Katus, Hugo; Karle, Christoph; et al. (Naunyn-Schmiedeberg's archives of pharmacology, 2007)
β3-adrenoceptors have recently been shown to induce a complex modulation of intracellular signaling pathways including cyclic guanine monophosphate, cyclic adenosine monophosphate, Nitric oxide, and protein kinases A and C. They are expressed in a broad variety of tissues including the myocardium, vascular smooth muscle, and endothelium. In those tissues, resting membrane potential is controlled mainly by inwardly rectifying potassium channels of the Kir2 family namely, Kir2.1 in the vascular smooth muscle, Kir2.1-2.3 in the myocardium, and Kir2.1-2.2 in the endothelium. In the present study, we investigated the possible modulation of Kir2 channel function by β3-adrenoceptors in an expression system. Human-cloned β3-adrenoceptors and Kir2.1 (KCNJ2), Kir2.2 (KCNJ12), and Kir2.3 (KCNJ4) channels were coexpressed in Xenopus oocytes, and currents were measured with double-microelectrode voltage clamp. Activation of β3-adrenoceptors with isoproterenol resulted in markedly increased currents in Kir2.1 and in Kir2.2 potassium channels with EC50 values of 27 and 18 nM, respectively. In contrast, Kir2.3 currents were not modulated. Coapplication of specific inhibitors of protein kinase A (KT-5720) and calmodulin kinase II (KN-93) had no effects on the observed regulation in Kir2.1. However, coapplication of protein kinase C (PKC) inhibitors staurosporine and chelerythrine suppressed the observed effect. In Kir2.2, coapplication of KT-5720 reduced the effect of β3-adrenoceptor activation. No differences in current increase after application of isoproterenol were observed between mutant Kir2.2 potassium channels lacking all functional PKC phosphorylation sites and Kir2.2 wild-type channels. In heteromeric Kir2.x channels, all types of heteromers were activated. The effect was most pronounced in Kir2.1/Kir2.2 and in Kir2.2/Kir2.3 channels. In summary, homomeric and heteromeric Kir2.x channels are activated by β3-adrenoceptors via different protein kinase-dependent pathways: Kir2.1 subunits are modulated by PKC, whereas Kir2.2 is modulated by protein kinase A. In heteromeric composition, a marked activation of currents can be observed particularly with involvement of Kir2.2 subunits. This regulation may contribute to the hyperpolarizing effects of β3-adrenoceptors in tissues that exhibit modulation by Kir2 channel function.
Gesehen am 13.01.2025